2012
DOI: 10.1021/cs300682d
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Selective Aerobic Oxidation of Amines to Imines by Gold Nanoparticle-Loaded Rutile Titanium(IV) Oxide Plasmon Photocatalyst

Abstract: Among various metal oxide-supported Au nanoparticles, Au/rutile TiO2 exhibits a particularly high level of visible-light activity for aerobic oxidation of amines to yield the corresponding imines on a synthetic scale with high selectivity (>99%) at 298 K. Experimental results have suggested that the reaction proceeds via the localized surface plasmon resonance-excited electron transfer from the Au nanoparticle to the TiO2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
134
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 178 publications
(138 citation statements)
references
References 29 publications
4
134
0
Order By: Relevance
“…5. It is clearly shown that the photogenerated electrons of α-Fe 2 O 3 will be excited from VB to its different energy-level CB position under visible irradiation, including high-energy region (−0.05 eV ~ −1.0 eV vs SHE) and low-energy region (0.1 eV ~ −0.05 eV vs SHE) in this system21. Thus, the photogenerated electrons at low-energy level would quickly relax to the VB bottom of α-Fe 2 O 3 , then to recombine with holes.…”
Section: Discussionmentioning
confidence: 85%
“…5. It is clearly shown that the photogenerated electrons of α-Fe 2 O 3 will be excited from VB to its different energy-level CB position under visible irradiation, including high-energy region (−0.05 eV ~ −1.0 eV vs SHE) and low-energy region (0.1 eV ~ −0.05 eV vs SHE) in this system21. Thus, the photogenerated electrons at low-energy level would quickly relax to the VB bottom of α-Fe 2 O 3 , then to recombine with holes.…”
Section: Discussionmentioning
confidence: 85%
“…Simultaneously, electrons injected into TiO 2 CB reduce O 2 preventing charge recombination. This highlighted that the synergy of anodic (amines oxidation) and cathodic (O 2 reduction) reactions was essential for the overall mechanism to proceed [112].…”
Section: Plasmon-enhanced Oxidation Reactionsmentioning
confidence: 99%
“…However, there are already several examples that demonstrate the viability of using SC photocatalysts to induce organic transformations . Some specific reactions promoted by TiO 2 are the oxidation of aliphatic and aromatic systems, or alcohols; the conversion of lactic acid into acetaldehyde; the synthesis of α‐chloro aryl ketones from aryldiazonium salts and terminal alkynes; Ullmann reactions; the conversion of amines to imines; the N‐alkylation of amines with alcohols; the addition of amines to deficient alkenes; heterocyclic functionalizations; the Huisgen [3+2] cycloaddition of azides and alkynes; or the addition of thiols to alkenes …”
Section: Photocatalytic Use Of Tio2 Nanomaterials In Aqueous and Biolmentioning
confidence: 99%